(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2024)
Background: Blood Methamphetamine levels have been utilized to assess methamphetamine exposure and its toxicity. Heart is a major target organ of methamphetamine intoxication. In some autopsy cases heart pathologies have been revealed at low level of methamphetamine and extensively to be understand a relationship between the blood methamphetamine level and heart pathology. Aim: The aim of this study was to assess the relationship between blood methamphetamine level and heart pathology by using postmortem cases. Methodology: One hundred and twenty medico-legal cases were included and blood methamphetamine or amphetamine levels in whole blood along with heart pathological finding were determined. Results: Coronary atherosclerosis, myocardial fiber hypertrophy, and fibrosis of the left ventricular myocardium were highly frequency findings in methamphetamine intoxication. Interestingly, forensic cases revealed myocardial fiber hypertrophy in chronic methamphetamine users. Conclusion: The levels of methamphetamine and amphetamine associated with myocarditis, cardiomyopathy and dystrophic calcification mitral valve. Evaluation of methamphetamine and amphetamine levels are key biomarkers for predicting the seriousness of heart-related pathological conditions.